Garden City lamb feeding experiments - Menzies, C.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2011)
The 600 head of Rambouillet wether feeder lambs used in these tests were received at Menard, Texas, October 10, 1960. They were sorted from 1100 wether lambs raised by Page Brothers of El Dorado, Texas. Average purchase weight was 75.1 pounds. Purchase price was $14.50 per cwt. The lambs were sheared at Menard, averaging 3.9 pounds of wool that sold for $0.41 ½ per pound. Lambs weighed 62.7 pounds off trucks at Garden City October 12th. Total trucking cost was $482.40.
Keywords: Sheep; Sorghum; Corn; Grain sorghum